Speed control of three-phase induction motors by changing air-gap flux - Dinçer, Gönül. (Thesis (M.S.) - Robert College. Faculty of Graduate School of Engineering, 1965., 1965)
In this paper the speed control of three-phase induction motors by changing the air-gap flux is studied with D.C or Singlephase A.C voltage applied to the auxiliary stator winding. In parts A and B the theoretical concept underlying the experimental results had been explained for both D.C and singlephase A.C control cases. In parts C, D and E experimental studies and results are discussed. D.C voltage applied to the auxiliary stator winding with six or twelve poles proved to be more convenient for the speed control. The theoretical and experimental studies indicates the possibility of a smooth speed control method for three-phase induction motors within certain limits.
Keywords: Electric motors, Induction.